Magnetic chemically peculiar stars investigated by the Solar Mass Ejection Imager. Issue 3 (6th May 2021) - Paunzen, E; Supíková, J; Bernhard, K; Hümmerich, S; Prišegen, M
ABSTRACT: Since the discovery of the spectral peculiarities of their prototype α 2 Canum Venaticorum in 1897, the so-called ACV variables, which are comprised of several groups of chemically peculiar stars of the upper main sequence, have been the target of numerous photometric and spectroscopic studies. Especially for the brighter ACV variables, continuous observations over about a century are available, which are important to study long-term effects such as period changes or magnetic cycles in these objects. This work presents an analysis of 165 Ap/CP2 and He-weak/CP4 stars using light curves obtained by the Solar Mass Ejection Imager (SMEI) between the years 2003 and 2011. These data fill an important gap in observations for bright ACV variables between the Hipparcos and TESS satellite missions. Using specifically tailored data treatment and period search approaches, we find variability in the accuracy limit of the employed data in 84 objects. The derived periods are in excellent agreement with the literature; for one star, the here presented solution represents the first published period. We discuss the apparently constant stars and the corresponding level of non-variability. From an investigation of our target star sample in the Hertzsprung–Russell diagram, we deduce ages between 100 Myr and 1 Gyr for the majority of our sample stars. Our results support that the variable CP2/4 stars are in a more advanced evolutionary state and that He and Si peculiarities, preferentially found in the hotter, and thus more massive, CP stars, produce larger spots or spots of higher contrast.